Household Resource Affected by Acute Diarrhea in Young Children - Plaitho, Jiraporn; Poonawakool, Uri (Journal of Health Science of Thailand, 2019)
Acute diarrhea is a major cause of morbidity among less-than-five-year Thai children. There are potential interventions to prevent diarrhea. Decision on the prevention depended on several factors and particularly the expense of household. This study estimated household cost that occur when the child was hospitalized with diarrhea. The questionnaire was developed and the caretakers were interviewed face-to-face during admission. Cases were less than five year children who were hospitalized with acute diarrhea from July 2002 to April 2003. There were 131 cases enrolled in this study. The median age was a year and a month. Fifty-nine percent had been covered by health insurance schemes while thirty-seven percent paid out of their pockets. The median duration of illness and admission were 4 and 3 days respectively. The median costs of acute diarrhea associated with pre-hospitalization, hospitalization and post-hospitalization were 100, 1,230 and 0 baht respectively. The median household expenditure was 1,428 baht per episode of acute diarrhea or 1.8 percent of the annual income. The main costs were traveling expense, boarding expense and earnings loss of caretakers and parents. This household cost could represent only for acute diarrhea in young children in Chanthaburi province. Further studies are needed in other areas to portray the real household costs of acute diarrhea among young children.